2014
DOI: 10.1021/ja500445z
|View full text |Cite
|
Sign up to set email alerts
|

ILQINS Hexapeptide, Identified in Lysozyme Left-Handed Helical Ribbons and Nanotubes, Forms Right-Handed Helical Ribbons and Crystals

Abstract: Amyloid fibrils are implicated in over 20 neurodegenerative diseases. The mechanisms of fibril structuring and formation are not only of medical and biological importance but are also relevant for material science and nanotechnologies due to the unique structural and physical properties of amyloids. We previously found that hen egg white lysozyme, homologous to the disease-related human lysozyme, can form left-handed giant ribbons, closing into nanotubes. By using matrix-assisted laser desorption ionization ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
131
1
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 89 publications
(144 citation statements)
references
References 64 publications
10
131
1
2
Order By: Relevance
“…Likewise, Lara et al recently found the shorter peptide sequence ILQINS to be highly amyloidogenic at room temperature. 53 This region of the protein is partially embedded inside the HEWL structure as a pocket in the junction connecting the α-domain and the β-domain. Combined with results from previous studies, our findings in this work indicated that the stability of this region in the β-domain directly determines the aggregation fate of the entire protein, dictating whether it proceeds to form amorphous aggregates or amyloid fibril.…”
Section: ■ Discussionmentioning
confidence: 99%
“…Likewise, Lara et al recently found the shorter peptide sequence ILQINS to be highly amyloidogenic at room temperature. 53 This region of the protein is partially embedded inside the HEWL structure as a pocket in the junction connecting the α-domain and the β-domain. Combined with results from previous studies, our findings in this work indicated that the stability of this region in the β-domain directly determines the aggregation fate of the entire protein, dictating whether it proceeds to form amorphous aggregates or amyloid fibril.…”
Section: ■ Discussionmentioning
confidence: 99%
“…ForLPF hydrogel, negative Cotton effects were observed at 268 and 316 nm ( Figure 2a;S upporting Information, Figure S7a). LPF/Tb 3+ gel also exhibited two negative Cotton effects.Inthe presence of Li + ,N a + ,C o 2+ ,N i 2+ ,C u 2+ ,Z n 2+ ,C d 2+ ,M n 2+ ,M g 2+ ,C a 2+ , and Al 3+ metal ions,C Ds ignals remained profiles of plain LPF assembly (Supporting Information, Figure S8a,c), which are contrary with SEM results.T he reason may be that the terminal interaction of the gelators plays an important role in defining the morphology of the assemblies [10] and, in contrast, their characteristic CD signals without inversion was mainly determined by the chirality of phenylalanine. [11] Furthermore, CD signal intensities were different at the same equimolar concentration of different metal ions,i ndicating different coordination efficiencies.W eak CD signals were observed when metal ions such as Ag + ,Ba 2+ ,F e 3+ ,and Eu 3+ existed in LPF gels (Supporting Information, Figure S8b,d).…”
mentioning
confidence: 99%
“…The fragment itself also forms fibrillar structures when incubated at room temperature and pH 2.0. Interestingly, the ribbons from this fragment show a right‐handed twist, whereas ribbons formed from LYS are left‐handed (Lara et al., ).…”
Section: Hen Egg Proteinsmentioning
confidence: 99%